Martensitic transformation within nanotwins enhances fatigue damage resistance of a nanotwinned austenitic stainless steel. (15th January 2022) - Li, Q.; Liu, D.Y.; Yan, F.K.; Tao, N.R.
Abstract: We investigated the low-cycle fatigue behavior of a novel nanotwinned 316L stainless steel consisting of nanotwinned austenitic grains embedded in the matrix with characteristic dislocation arrangements. We excitingly found that the α′-martensitic transformation is activated traversing twin lamellae to undertake the localized deformation of nanotwinned grains at high strain amplitudes. These α′-martensite nuclei are mainly originated from the intersections between "zigzag" slip bands and twin lamellae. Thanks to the effective release of stress/strain localization by the α′-martensitic transformation within nanotwins, the fatigue strength and fatigue life in the low-cycle regime are simultaneously enhanced. Graphical abstract: Image, graphical abstract